2015
DOI: 10.3390/molecules20059183
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, Inflammation, and Chronic Diseases: How Are They Linked?

Abstract: It is extensively verified that continued oxidative stress and oxidative damage may lead to chronic inflammation, which in turn can mediate most chronic diseases including cancer, diabetes, cardiovascular, neurological, inflammatory bowel disease and pulmonary diseases. Curcumin, a yellow coloring agent extracted from turmeric, shows strong anti-oxidative and anti-inflammatory activities when used as a remedy for the prevention and treatment of chronic diseases. How oxidative stress activates inflammatory path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
330
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(350 citation statements)
references
References 193 publications
5
330
0
15
Order By: Relevance
“…Curcumin has been demonstrated to exert pleotropic beneficial functions, including antioxidative and anticancer effects (3)(4)(5). In addition, several previous studies have demonstrated that curcumin promotes apoptosis and inhibits the proliferation of pancreatic cancer cells (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has been demonstrated to exert pleotropic beneficial functions, including antioxidative and anticancer effects (3)(4)(5). In addition, several previous studies have demonstrated that curcumin promotes apoptosis and inhibits the proliferation of pancreatic cancer cells (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…CUR is known to exhibit a wide range of effects including anti-inflammatory, antitumor, and lipid-lowering activities, which are attributed primarily to its potent antioxidant capacity. [1][2][3] However, CUR's ability to exert these biological effects in vivo is undermined by its low bioavailability due to …”
Section: Introductionmentioning
confidence: 99%
“…In 1910, following the elucidation of the chemical structure of double feruloyl methane, research into the physiological and pharmacological effects of curcumin made marked progress (11). Curcumin has been demonstrated to exhibit anti-inflammatory, antioxidant, lipid-lowering, antivirus, anti-infection, anti-tumor, anti-liver fibrosis and anti-atherosclerosis effects, in addition to other pharmacological activity; furthermore, curcumin demonstrates low toxicity without serious adverse reactions (11,12). It has been demonstrated that the underlying molecular mechanism of the anti-tumor effects of curcumin primarily involves apoptosis of tumor cells, inhibition of the signal transduction pathway of tumor cell growth, oxidationresistance and inhibition of tumor angiogenesis (13).…”
Section: Introductionmentioning
confidence: 99%